Shared identity content between leader and follower influences intentional mobilization and challenge and threat states. (May 2021) - Miller, Anthony J.; Slater, Matthew J.; Turner, Martin J.
Abstract: Objectives: Researchers have examined how leaders' representation of shared identity content allows them to mobilize group members towards success in competitive tasks. However, research is yet to determine the psychological and physiological implications of shared identity content with a leader when approaching competitive tasks. The present research addresses this gap within a two-phase experimental study, examining the effect of shared identity content on follower intentional mobilization, self-efficacy, perceived control, approach and avoidance goals, cardiovascular challenge and threat and motor performance within a competitive task. Design: A 2 × 2 between-participants two-phase experimental design, with two shared and two non-shared conditions. Method: Within phase one, 220 sport and exercise undergraduate students imagined themselves in one of four scenarios and responded to measures of mobilization (e.g., willingness to invest time on a task). Then, a pre-screening questionnaire was used to evidence the students' authentic identity content when competing in sport, which informed condition within phase two. Of those who consented to phase two, a laboratory experiment with 120 undergraduate sport and exercise students was used. Within this experiment, the sharedness of identity content between leader and follower was manipulated through the students' authentic pre-screening questionnaire responses. Within phase two, competition related self-efficacy, perceived control, approach and avoidance goals, cardiovascular challenge and threat and motor performance was assessed. Results: Phase one results indicated that when identity content is shared (vs. non-shared) between leader and follower, group members' willingness to invest time on a task is increased within a hypothetical scenario. In phase two, it was evidenced that when identity content is shared (vs. non-shared) between leader and follower, followers reported greater intentional mobilization, self-efficacy and perceived control when approaching a competitive task. Shared identity content with a leader did not predict cardiovascular challenge states nor greater motor performance (relative to non-shared identity content). Conclusion: The present research provides evidence that a leaders' capacity to mobilize effort of group members and enhance psychological appraisal of competitive events is dependent on their ability to build shared identity content. Highlights: Shared identity content increases intentional mobilization. Shared identity content promotes positive appraisals of competitive events. Shared identity content does not influence cardiovascular responses. Shared identity content does not influence competitive motor performance.